Dynamic Time Warping fixed - frame coefficient with pitch feature for speech recognition system with neural network [electronic resource] - 414128 Rubita Sudirman; Fakulti Kejuruteraan Elektrik (2007)
Thesis (Ph.D (Kejuruteraan Elektrik)) - Universiti Teknologi Malaysia, 2007